Analyzing Academic Essays Written by EFL Students Focusing on Transition Signals - Alnefaie, Mashael Abdullah; Jama, Itithaz Abdullah (Journal of language teaching and research, 2025)
The study’s sampling consisted of fifteen participants who majored in applied linguistics. The students took two grammar and English writing courses that exposed them to different types of cohesive devices to enhance the readability of written paragraphs. The authors collected three types of essays from the students: argumentative, compare and contrast, and cause and effect. This study uses a qualitative research methodology to understand EFL students’ recognition of the use of transition words by applying the Freeman theory in teaching grammar; it focuses on meaning, form, and usage. The authors collected fifteen written samples that illustrate different types of essays. The data are analyzed using the thematic method of reading the data and identifying three themes. The results show that EFL students apply a few of the most familiar transition signals in writing argumentative, compare-and-contrast, and cause-and-effect essays. Regardless of the type of academic essay, the data reveal that the EFL students needed help with using varied or unfamiliar transition words due to their limited knowledge of the meaning and the use of each transition signal in relation to each type of essay. Finally, this study offers various recommendations to develop an awareness of teaching and learning the transition signals from the perspective of Freeman’s three dimensions.